Forums on Rural Women and Equity During the COVID-19 Pandemic - Instituto Interamericano de Cooperación para la Agricultura (IICA) (2020)
Participants: -Carmen Nurse, of the Caribbean Network of Rural Women Producers (CANROP). -Tania Lieuw-a-Soe, of the Wi Uma FU Sranan/Suriname Network of Rural Women Producers. -Gillian Goddard, of the Alliance of Rural Communities (ARCTT). -Tamisha Lee, President of the Jamaica Network of Rural Women Producers (JNRWP). -Jennifer Spencer, Coordinator of the Women Agro-processors Development Network (WADN). -Shauna Brandon, IICA Specialist in the Jamaica Office. - Ann-Marie Williams, Gender Specialist, CARICOM Secretariat.